2010
DOI: 10.1088/0004-637x/725/1/1111
|View full text |Cite
|
Sign up to set email alerts
|

Formation Pumping of Molecular Hydrogen in Dark Clouds

Abstract: Many theoretical and laboratory studies predict H 2 to be formed in highly excited ro-vibrational states. The consequent relaxation of excited levels via a cascade of infrared transitions might be observable in emission from suitable interstellar regions. In this work, we model H 2 formation pumping in standard dense clouds, taking into account the H/H 2 transition zone, through an accurate description of chemistry and radiative transfer. The model includes recent laboratory data on H 2 formation, as well as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 58 publications
4
32
0
Order By: Relevance
“…Le Bourlot et al (1995a) showed that the excitation due to the secondary electrons generated by cosmic rays was much more efficient, even for the standard value of the cosmic ionization rate. Similar conclusions were reached by Islam et al (2010) in a detailed modeling study including the most recent experimental information on the excitation of H 2 and assuming however the "standard" formation rate of 3 ×10 −17 n H n(H) cm 3 s −1 . Congiu et al (2009) also found that internal excitation is quenched before desorption from experiments involving amorphous water ice.…”
Section: H 2 Excitation In the Formation Processsupporting
confidence: 78%
See 3 more Smart Citations
“…Le Bourlot et al (1995a) showed that the excitation due to the secondary electrons generated by cosmic rays was much more efficient, even for the standard value of the cosmic ionization rate. Similar conclusions were reached by Islam et al (2010) in a detailed modeling study including the most recent experimental information on the excitation of H 2 and assuming however the "standard" formation rate of 3 ×10 −17 n H n(H) cm 3 s −1 . Congiu et al (2009) also found that internal excitation is quenched before desorption from experiments involving amorphous water ice.…”
Section: H 2 Excitation In the Formation Processsupporting
confidence: 78%
“…Models labelled "A" correspond to a fixed formation rate of molecular hydrogen of 3 × 10 −17 cm 3 s −1 , following the prescriptions of Hollenbach et al (2009) and Islam et al (2010); in models "B", H 2 is formed only by LH mechanism, and in models "C" both the LH and ER mechanisms are activated to form H 2 . The model geometry is a plane parallel infinite slab with an isotropic radiation field impinging on both sides.…”
Section: Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9a'' signifies that the starting 2H chem configuration is that of Fig. We also include data calculated for C2/C1 adsorption of two H atoms on the (MgO) 6 cluster, the nano-olivine_b and nano-olivine_c clusters based on the initial C2-type H adsorptions shown in Fig. 5e.…”
Section: Formation Of Hmentioning
confidence: 99%